SANCTIONING HATE SPEECH ON THE INTERNET: IN SEARCH OF THE BEST APPROACH - Antic, Petar (Pravni zapisi, 2023)
The borderless nature of the Internet, different national approaches to the understanding of what constitutes hate speech, as well as the danger of restrictions on the freedom of speech, make it difficult to develop appropriate mechanisms against this phenomenon. The limitations of international law in providing a universal definition of hate speech, due to the different national approaches to freedom of expression, have thwarted attempts to produce an effective international treaty in order to deal with this issue. Imposing obligations on Internet portals to establish self-regulatory mechanisms for removing hate speech content has raised concerns of non-competent censorship and potential limitations of the freedom of expression. This paper focuses on the challenges encountered in the struggle against hate speech online and possible mechanisms for combating this phenomenon.
Keywords: hate speech; freedom of expression; Internet; online; media; dissemination